Analisis Partisipasi Keluarga dalam Undang-Undang Tindak Pidana Kekerasan Seksual Perspektif Hukum Islam - Muhammad Handika Suryanto (Jurnal Kawakib, 2023)
Cases of sexual violence from year to year are increasing and troubling the Indonesian people. The government's response was to pass the Sexual Violence Act, in which there is an important role for family participation. So, the aims are: (1) To describe family participation in the Sexual Violence Crime Law and (2) To analyze Family Participation in the Sexual Violence Crime Law based on the perspective of Islamic Law. This research method is qualitatively normative with the study of center. The results there were 6 points of family participation analyzed by Islamic law. The analysis of family participation in article 86 of the Sexual Violence Crime Law from the perspective of Islamic law is sourced from the Qur'an Surat As-Saffat verse 102 and Al-Isra’ verse 32. And also from Bukhari Hadith number 5538 and number 4801. And the last from qawaid fiqh about eliminating mudharatan.